THE RESULTS OF USE OF NEW NATIVE THROMBOLYTIC IN CLINICAL PRACTICE - E. S. Mazur; R. M. Rabinovich; V. V. Mazur; N. S. Kuznetsova; E. A. Kudryashova; S. V. Veselov (Столичная издательская компания, 2016)
Aim. To assess the efficacy of thrombolytic Fortelyzin in ST elevation myocardial infarction (STEMI) in real clinical practice.Material and methods. Fortelyzin was administered intravenously to 38 patients with STEMI with follow-up assessment of reperfusion success by ECG and angiographic criteria. Bleedings, anaphylaxis and total mortality were considered.Results. The ST-segment resolution up to 70% in 180 min was reached in 66% of patients and angiographic effect TIMI 2-3 - in 60% of patients. The major bleeding rate was 2.6%, allergic reactions - 0%, total mortality - 10.5%. Unsuccessful reperfusion was observed more frequently in patients with ECG ischemia of grade 3 and with angiographic visualization of the collateral blood flow.Conclusion. The general efficacy of Fortelyzin in real clinical practice was 73%. ECG ischemia of grade 3 and the presence of angiographic collateral blood flow predict unsuccessful reperfusion of the infarct-related artery.